Experimental evidence from intensified placement efforts among unemployed in Sweden - Pathric Hägglund (Institute for Labour Market Policy Evaluation (IFAU), 2009)
This paper uses experimental data to study the effects of participation in intensified placement efforts on subsequent job chances and earnings. Five small-scale experiments were performed in four different regions of Sweden in 2004 and the control groups were offered the PES regular services. Due to small samples, many of the impact estimates were imprecise and insignificant. However, the services generally reduced unemploy-ment among the treated. I find significantly enhanced exits to either jobs or other acti-vities (or both) in four of the experiments. Three of the experiments also report positive effects on employment probability and earnings in the years following the programme. Finally, combining job-search assistance and monitoring of job search generated signifi-cantly better results than monitoring alone in one of the experiment locations.
Keywords: C93; J64; 330; Active labour market policy evaluation; randomised social experiment; placement efforts; Arbeitsmarktpolitik; Arbeitsplatzsuchmodell; Wirkungsanalyse; Feldforschung; Schweden